1H, 29Si and 119Sn double and triple resonance NMR spectroscopy of the small-pore framework sodium stannosilicate Na2SnSi3O9·2H2O - da Silva, Danilo Antonio [UNESP]; Greiser, Sebastian; Contro, Janine [UNESP]; Medeiros, Vinicius Litrenta [UNESP]; Nery, José Geraldo [UNESP]; Jaeger, Christian (Elsevier, 2020)
The small-pore framework sodium stannosilicate AV-10, chemical composition Na2SnSi3O9·2H2O and known crystallographic structure, was synthesized by hydrothermal crystallization. This stannosilicate is built up of a three-dimensional network of corner-shared SiO4 tetrahedra and SnO6 octahedra. The SnO6 sites are linked to six SiO4 tetrahedra (Sn(6Si)) while each of the two crystallographically different SiO4 units are connected to two SnO6 and SiO4 units (Si(2Si,2Sn)). This material was used as model compound for developing a solid-state MAS NMR strategy aimed on the challenges and possibilities for structural studies, particularly considering the short and medium range order to verify the connectivity of SiO4 and SnO6 of such compounds despite the low natural abundances of 4.68% for 29Si and 8.59% for 119Sn nuclei as a real challenge. 29Si{119Sn} and 119Sn{29Si} REDOR (Rotational-Echo Double-Resonance) NMR measurements after 1H cross-polarization (CP) were carried out. The REDOR curves show a significant change after the “normal” quadratic short time evolution from which both (i) the shortest internuclear 29Si – 119Sn distances (and vice versa) and (ii) the number of corner-sharing SiO4 tetrahedra around the SnO6 octahedra (and vice versa) can be obtained. Based on these data, optimized 29Si{119Sn} and 119Sn{29Si} REPT-HMQC (Recoupled Polarization Transfer-Heteronuclear Multiple-Quantum Correlation, again after 1H CP) experiments were implemented, which directly show those heterogroup connectivity as correlation peaks in a 2D spectrum. This information was also obtained using 2D29Si{119Sn}-J-Coupling NMR experiments. Furthermore, 2D29Si INADEQUATE NMR experiments are also feasible, showing the connectivity of SiO4 tetrahedra. The combination of REDOR, REPT-HMQC, J-Coupling and INADEQUATE experiments yielded a complete analysis of the short and medium range structure of this microporous stannosilicate, in agreement with the previously published structure obtained Ab Initio from powder X-Ray diffraction data (XRD).
Keywords: 1H{29Si} and 1H{119Sn} cross-polarization; 29Si{119Sn} double resonance; INADEQUATE; REDOR; REPT-HMQC; Stannosilicates